A Strategy for Consumer Protection in Pakistan (The Pakistan Development Review, 1996)
Government is relying increasingly on the market mechanism for economic management. The underlying perfect competition model assures maximum welfare of consumer, but assumptions of the model do not hold in real world. Consumer is central to economic activity but at the same time is vulnerable to exploitation by producers, misleading information, ignorance of his rights and non-availability of redress mechanism. Markets may be competitive but the consumers may suffer on account of imperfect information, search and transport costs needed to make satisfactory choices. This creates the need for government intervention for protecting the consumer welfare and rights. This paper explains why a consumer protection policy is needed in a situation of ‘competitive’ markets and looks into consumer protection strategies followed in some other countries. The area of consumer protection in Pakistan has remained neglected so far and no meaningful effort has been made in this direction. Realising this gap, the paper chalks out a consumer protection strategy for Pakistan; which goes beyond mere formulation of legislation and also includes consistent efforts towards awareness creation, provision of information/advice, setting of quality standards and redress. In the long run the efforts should continue in the from of research, formation/strengthening of consumer pressure groups and regional cooperation.